The Relationship Between Dividend Announcements And Ex-Dividend Dates On Stock Prices Before And During The Pandemic In The Indonesian Stock Market - Weli Weli; Christabella Handayani (UNIB Press, 2024)
The ongoing discourse surrounding the ramifications of dividend announcements and ex-dividend dates on stock prices persists, particularly against the backdrop of the Covid-19 pandemic's significant upheaval on the Indonesian economy, including its stock market. Thus, this study endeavors to delve into the intricate dynamics of how dividend announcements and ex-dividend dates influence stock prices, coupled with an exploration of investor reactions amidst the pandemic. Focusing on companies listed on the IDX that dispensed dividends from 2018 to 2021, this research adopts a purposive sampling approach, yielding a robust dataset comprising 181 observations. Leveraging descriptive analysis and hypothesis testing via SPSS software, the study unravels compelling insights. Notably, it unveils a positive nexus between dividend announcements, the pandemic, and stock prices. Intriguingly, however, the ex-dividend date appears to exert negligible impact on stock prices, challenging conventional wisdom. By shedding light on these dynamics, this research contributes to a deeper understanding of market behavior amidst dividend-related events and the unprecedented disruptions posed by the Covid-19 pandemic, offering valuable insights for investors and policymakers.